Safety and Efficacy of Bull’s-Eye versus Triangulation Technique for Percutaneous Nephrolithotomy in Bangladesh (IAHS Medical Journal, 2024)
Background: Percutaneous Nephrolithotomy (PCNL) has underwent considerable evolution, which has been driven by advances in access techniques, instrumentation and endoscopic technology. Renal access can be achieved by ultrasonography, fluoroscopy and Computed Tomography guidance. Access under fluoroscopy can be achieved by ‘Triangulation’ or ‘Eye of the needle’ (Bull's eye) techniques. This study was conducted to evaluate the safety and efficacy of both these techniques.Materials and methods: This quasi experimental study was conducted at the Department of Urology, Chittagong Medical College Hospital, Chattogram. A total 136 patients were selected with renal calculi (2-4cm), considering the inclusion and exclusion criteria. Among these, half of the patients were included in group A (Bull’s-eye technique) and rest of the patients were in group B (Triangulation technique) using Simple random table. After proper counseling and written informed consent, all patients underwent PCNL under general anesthesia. On postoperative day 2, a plain X-ray was obtained to document stone clearance. Close follow up and recording was done to search for any complications. Stata (V.16) software was used for the analysis.Results: The baseline characteristics (Age, sex, BMI, stone size and stone location) of the patients in group A and group B were almost similar. In the present study, stone free rate was 92.64% in group A and 91.18% in group B (p=0.75), statistically insignificant between groups according to stone size and stone location. Mean access time of group A was 1.69±0.49 mins and that of group B was 2.22±0.24 mins. The mean fluoroscopy time (Min) for access in group A was 1.00±0.26 mins and the that of group B was 1.47±0.56 mins. Both access time and fluoroscopy time for access were significantly lower in Bull’s-eye techniques for PCNL (p